Balian River as an Inspiration for the Creation of Jantra Bhinawa Neurological Music - Yudana, I Gede; Yudarta, I Gede; Ardini, Ni Wayan (Journal of Music Science, Technology, and Industry, 2025)
Purpose: The large number of psychiatric cases experienced by teenagers today raises great concerns about their future. To overcome this, there are many things that can be done, one of which is art therapy. Balian River in Pupuan Village, Tabanan, Bali, Indonesia, was used as a source of inspiration for the creation of neurological music with the title Jantra Bhinawa. This study was created to analyze Balian River as an inspiration for the creation of Jantra Bhinawa neurological music for the benefit of art therapy itself. Reseach methods: This creation uses a method of creating works of art based on qualitative and quantitative research. Data collection was carried out by means of surveys, literature studies, interviews, noise measurements and frequency measurements. Results and discussion: One part of art therapy that can be applied is low frequency music therapy such as red or brown noise. Noise is useful for improving concentration and sound sleep. This is generally produced by natural sounds such as waterfalls and river water in Balian River. Implication: Neo-Guntang as a medium of expression uses a neurological musical approach framed by karawitan artwork to convey the ideas of Balian River itself.